Prognostic factors in intramedullary astrocytomas: a literature review - Benes, Vladimír; Barsa, Pavel; Benes, Vladimír; Suchomel, Petr (European spine journal, 2009)
Astrocytomas affect a significant portion of patients with intramedullary tumors. These infiltratively growing tumors are treated by a variety of methods -- biopsy and decompressive surgery, maximal safe resection, adjuvant oncological therapy. Also, numerous prognostic factors are reported in the literature. Better understanding of factors that influence prognosis may help in treatment planning with the goal of prolonging survival. We have thus undertaken an extensive literature review in order to define factors affecting prognosis. A total of 38 articles were studied. Only tumor grade was consistently reported as the major factor affecting prognosis. The influence of other clinical factors (age, gender, history length, functional status, tumor location or extent, syrinx or cyst presence) can be speculated upon, but cannot be assessed adequately from the available literature. For both low- and high-grade (HG) astrocytomas, maximal safe tumor resection should be the primary treatment objective but is often not feasible in contrast to other intramedullary and spinal neoplasms. Since the biological nature of spinal cord HG glioma is identical to that of the brain, the same treatment algorithm of maximal safe resection followed by concomitant radio- and chemotherapy would be sensible to implement.
Keywords: Neurosurgical Procedures; nádory míchy; invazivní růst nádoru; radioterapie; mícha; Neoplasm Invasiveness; Humans; farmakoterapie; astrocytom; lidé; Drug Therapy; Spinal Cord Neoplasms; neurochirurgické výkony; Spinal Cord; Prognosis; prognóza; Radiotherapy; Astrocytoma